Platform Oligopoly and Data Feudalization under the Perspective of Technological Sovereignty: Research on the Realization of Socialist Public Ownership - Lan, Yijie (International Journal of Social Sciences and Public Administration, 2025)
As a core element in safeguarding national sovereignty, "technological sovereignty" has evolved into technological feudalism through its exclusivity in the digital era, specifically manifested as a market pattern of platform oligopolies. Data feudalization serves as the hallmark feature of this phenomenon. Grounded in Marxist monopoly theory and technological sovereignty, this paper systematically analyzes the formation mechanisms of platform oligopoly and the typical characteristics of "data feudalization," exploring their challenges and implications for realizing socialist public ownership in the digital economy. The study reveals that platform capital constructs new monopolistic forms through data possession, algorithmic control, and ecosystem closure - essentially perpetuating the logic of capital expansion. Meanwhile, "data feudalization" exacerbates digital economy inequality via data privatization and labor alienation. From an international comparative perspective, this paper proposes transforming platform economies from commercial market logic to social logic through socialist ownership-based approaches: market-oriented allocation of data elements, public ownership of digital infrastructure, and innovation in antitrust legal frameworks. This transformation ultimately achieves a dynamic equilibrium between technological sovereignty and public interests.